Evaluation of Economic Sustainability of Crop and Livestock Integrated Farming Systems Under Rainfed Agriculture (Indian Journal of Animal Production and Management, 2025)
Majority of the Indian economy is in the hands of small and marginal farmers with  80% of total land holdings having less than 1ha of cultivable land. Integration of  livestock with crop provides scope for effective utilization of byproducts which  assures the profitability of the farming system. Integrated Farming System approach  is required to enhance the living standards of the small and marginal farmers. The  present study revealed the profitable farming systems in major farming situations  and its diversification. It was observed that the farming system consisting of seasonal  crops along with dairy, sheep and poultry was found most profitable than cultivation  of crops alone. The economic sustainability of the faming systems was evolved  through Sustainability Value Index (SVI). Most of the farming systems in the rainfed  black soils were found sustainable. But only one farming system in rainfed red soils  was found sustainable.The Simpson Index of Diversification (SID) was also assessed  and observed more diversification in the farming systems under rainfed red soils. The  results of the study are useful for small and marginal farmers to adopt the suitable  farming system.
Keywords: Sustainable livelihoods; Integrated Farming System